Mode Analysis of Degree of Freedom of a New Bifurcation Parallel Mechanism - Song Wei; Xu Yong; Liu Yong; Lü Yeping; Liang Zheng (Jixie chuandong)
A new bifurcated single-loop closed-chain configuration URRC is proposed.This single-loop closed-chain has two degrees of freedom modes.A bifurcated parallel mechanism is obtained by combining series branch PRRP with bifurcated single-loop closed chain to form a hybrid branch chain and connecting the moving platform and fixed platform with three parallel branches.Through the combination of different modes of single-loop closed-chain，the parallel mechanisms of 3T3R，3T，2R1TⅠ，2R1TⅡ and 1R2T with five DOF modes are obtained.The correctness of the five DOF modes of the bifurcated parallel mechanism and the rationality of driving selection are proved by screw theory analysis.